SOCIOLOGY OF LITERATURE? WHAT IS THAT? LET’S READ GISÈLE SAPIRO - Montero Corrales, Cristopher (2021)
This text is a review of the book “The Sociology of Literature” of Gisèle Sapiro. She shows the forms of construction of an object of study between the sociology and the literature, as well the principles of teoric frames that have gotten into the thought of the literary text, his creation and the social reception. This was done gathering studies and thoughts that have use it as a social act. Finally with a piece of the emerging spaces of the literature of sociology. It results been an important consultant text for the sociological reflection of literature for the variety theorical explorations and different points of view on four chapters: Theory and Approaches sociological of the literature, The social conditions of the production of the pieces, The sociology of the pieces, and Sociology of reception.